Analisis Pendapatan Nelayan Ikan Roa (Hemirampidae/Julung) di Desa Kase Kecamatan Leksula Kabupaten Buru Selatan - Sigmarlatu, Stanly; Louhenapessy, William George Mozes; Sinay, Fransisca Riconita (Jurnal Pendidikan Ekonomi, 2023)
This study aims to analyze the income of roa fish (Hemirampidae/Julung) fishermen in Kase Village, Leksula District, South Buru Regency, where most residents depend on marine resources for their livelihood. Roa fish is a highly valued pelagic species and the region’s primary fishery commodity. The research adopts a descriptive qualitative approach, utilizing in-depth interviews and documentation involving 12 informants, consisting of six owner fishermen and six labor fishermen. Income analysis is based on net income calculation, defined as the difference between total revenue and total costs (fixed and variable). The findings reveal that owner fishermen earn significantly higher income due to their full control over fishing equipment, operational time, and direct sales. In contrast, labor fishermen receive moderate income, relying solely on a profit-sharing system and lacking influence in the production process. External factors such as fishing seasons, extreme weather, and market price fluctuations also considerably affect income levels. This research recommends government interventions including entrepreneurship training, access to capital, and strengthening fishermen cooperatives to foster economic self-reliance within coastal communities